IMPLEMENTING WORD WALL AS A MEDIA TO FACILITATE EFL STUDENTS IN LEARNING VOCABULARY - Ismaya, Imas; risudarso, Mansyur S; Puspitaloka, Nina (PROJECT (Professional Journal of English Education), 2024)
The present study aimed to explore the implementation of word walls as a media to facilitate EFL (English as a Foreign Language) students in vocabulary learning. Conducted at a junior high school in Bekasi, this qualitative research utilized a case study design. Data were collected through observations and interviews. The results demonstrated that using word walls to support EFL students in learning vocabulary positively impacts their English language acquisition, particularly in vocabulary, which is often a significant challenge for learners of English. The use of word walls offers several advantages, such as enhancing students' comprehension of English, introducing them to new vocabulary, and promoting active participation in classroom activities. This method of vocabulary instruction was a novel approach for the students. After its implementation, student feedback was overwhelmingly positive. They became more engaged in class, found the material easier to grasp, and experienced vocabulary learning as more enjoyable. The findings suggest that word walls are effective visual aids that improve vocabulary retention and create a more interactive learning atmosphere. Students reinforced their understanding of new words through visual cues, which increased their engagement and participation in classroom discussions.